It's showtime folks ; Doing more with less ; Real life : ADELA [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Features entertainers who became politicians. Their campaigns for the 1992 election with candidates Freddie Webb, Vicente Sotto III and Joseph Estrada. Tackles on the UP-PGH services ; Shows the Adela sugar workers stage play. Zarzuela about the life of sugarcane workers at Hacienda Adela at Silay Negros Occidental.